2005
DOI: 10.3182/20050703-6-cz-1902.01433
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Lacquer Production by Reachability Analysis – A Case Study

Abstract: In this paper we describe a case study on lacquer production scheduling that was performed in the European IST-project AMETIST and was provided by one of the industrial partners. The approach is to derive schedules by means of reachability analysis: with this technique the search mechanism of model checkers, in our case here Uppaal, is used to find feasible or optimal schedules. The advantage of this approach is that the expressiveness of timed automata allows to model scheduling problems of different kinds, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…an optimal schedule. However, it was shown that this technique, extended by suitable heuristics, allows to find good schedules in very short time [5,6].…”
Section: Uppaal and Uppaal Coramentioning
confidence: 99%
See 2 more Smart Citations
“…an optimal schedule. However, it was shown that this technique, extended by suitable heuristics, allows to find good schedules in very short time [5,6].…”
Section: Uppaal and Uppaal Coramentioning
confidence: 99%
“…In earlier work [5,6] we experimented with several heuristics. In the current context, we used only greediness as strategy and restrict the number of orders that may be processed at any point in time.…”
Section: Uppaal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs are incurred during machine use, cleaning and storage (if recipes are fulfilled before the deadline). The Axxom case has been studied for schedulability with timed automata in [5] and for optimization in [13]. For a thorough introduction to the Axxom case study, we refer the reader to either of the two papers.…”
Section: Applicationsmentioning
confidence: 99%
“…PTA have proven useful for a wide range of different search problems such as model checking, [7], and scheduling, [1,5,18]. The diversity of applications and generality of the modelling language of PTA suggests that no single search algorithm is superior and, thus, could benefit from an agent-based approach to search.…”
Section: Introductionmentioning
confidence: 99%